Multicriteria Decision-Making under Conditions of Uncertainty : a Fuzzy Set Perspective - Ekel, Petr (Wiley, 2019)
A guide to the various models and methods to multicriteria decision-making in conditions of uncertainty presented in a systematic approach Multicriteria Decision-Making under Conditions of Uncertainty'presents approaches that help to answer the fundamental questions at the center of all decision-making problems: "What to do'" and "How to do it'" The book explores methods of representing and handling diverse manifestations of the uncertainty factor and a multicriteria nature of problems that can arise in system design, planning, operation, and control. The authors'noted experts on the topic'and their book covers essential questions, including notions and fundamental concepts of fuzzy sets, models and methods of multiobjective as well as multiattribute decision-making, the classical approach to dealing with uncertainty of information and its generalization for analyzing multicriteria problems in condition of uncertainty, and more. This comprehensive book contains information on "harmonious solutions" in multiobjective problem-solving (analyzing X, F>'models), construction and analysis of X, 'R> models, results aimed at generating robust solutions in analyzing multicriteria problems under uncertainty, and more. In addition, the book includes illustrative examples of various applications, including real-world case studies related to the authors' various industrial projects. This important resource: -Explains the design and processing aspect of fuzzy sets, including construction of membership functions, fuzzy numbers, fuzzy relations, aggregation operations, and fuzzy sets transformations -Describes models of multiobjective decision-making (X.'M> models), their analysis on the basis of using the Bellman-Zadeh approach to decision-making in a fuzzy environment, and their diverse applications, including multicriteria allocation of resources -Investigates models of multiattribute decision-making (X, 'R> models) and their analysis on the basis of the construction and processing of fuzzy preference relations as well as demonstrating their applications to solve diverse classes of multiattribute problems -Explores notions of payoff matrices and fuzzy-set-based generalization and modification of the classic approach to decision-making under conditions of uncertainty to generate robust solutions in analyzing multicriteria problems' Written for students, researchers and practitioners in disciplines in which decision-making is of paramount relevance, 'Multicriteria Decision-Making under Conditions of Uncertainty'presents a systematic and current approach that encompasses a range of models and methods as well as new applications.'